2016
DOI: 10.1016/j.dld.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of gamma-glutamyl transferase in adult: Should we think about progressive familiar intrahepatic cholestasis?

Abstract: Disease and mechanisms that determine cholestasis are complex and their understanding may provide new therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Cholestasis and biliary tract injury present in PBC patients, and these conditions worsen as the disease progresses 9 , 19 . Furthermore, elevated GGT is a valuable indicator of bile duct obstruction 20 22 , which often manifests in PBC patients. We tested whether ALP or GGT levels correlated with serum or salivary AMA-M2.…”
Section: Resultsmentioning
confidence: 99%
“…Cholestasis and biliary tract injury present in PBC patients, and these conditions worsen as the disease progresses 9 , 19 . Furthermore, elevated GGT is a valuable indicator of bile duct obstruction 20 22 , which often manifests in PBC patients. We tested whether ALP or GGT levels correlated with serum or salivary AMA-M2.…”
Section: Resultsmentioning
confidence: 99%
“…[ 13 ] A prospective multicenter study assessed the efficacy and safety of the serotonin reuptake inhibitor sertraline, for the treatment of children with refractory cholestatic pruritus. [ 14 ] Oliveira et al [ 15 ] thought that the genetic defect in PFIC-3 appears to explains the pathogenesis of intrahepatic cholestasis in pregnancy; their understanding may might provide insights into for developing new therapeutics therapies. After analyzing >150 BSEP mutations, Dröge et al [ 16 ] demonstrated that the extent of exon skipping depends on the genomic and cellular contexts, and that regulation of splicing may have therapeutic potential for PFIC-2.…”
Section: Discussionmentioning
confidence: 99%
“…The association between PSC and variants in ABCB4 remains controversial although several case reports in adults allude to a possible association. [28][29][30] A study looking at the role of heterozygous variants in ABCB4 in 76 PBC and 46 PSC adult patients did not demonstrate any haplotype distribution and linkage disequilibrium in patients against healthy controls. 31 However, in a study of 32 adults with histologic evidence of cholestatic liver disease of unknown etiology 34% were found to have a heterozygous variant in ABCB4.…”
Section: The Possible Clinical Consequencesmentioning
confidence: 99%